1986
DOI: 10.1039/np9860300591
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and polyterpenoids

Abstract: Metabolism 2 Polyterpenoids and Quinones 2.1 Polyterpenoids 2.2 Isoprenylated Quinones 3 References [(3S,3'R) -3,3'dihydroxy -7',8'-didehydro-p,Pcaroten -4 -one] (20), the absolute configuration (3S,4R,3'R) of the mollusc NATURAL PRODUCT REPORTS, 1986 -G . BRITTON 1.3 Synthesis and Reactions ( 4 8 ) R ' = j , R 2 = i

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…A latitudinal analysis of the distribution of solar energy maxima during the year showed that in the northern hemisphere, the distribution of radiation maxima is symmetric for the month of June. So, July is symmetric to May, April to August, September is similar to March (points of autumn and spring equinox), October to February, November to January, and December in the southern hemisphere is an axis of symmetry, as well as June in the northern hemisphere (Britton, 1986).…”
Section: Qualitative Characteristics Of Solar Radiationmentioning
confidence: 99%
See 1 more Smart Citation
“…A latitudinal analysis of the distribution of solar energy maxima during the year showed that in the northern hemisphere, the distribution of radiation maxima is symmetric for the month of June. So, July is symmetric to May, April to August, September is similar to March (points of autumn and spring equinox), October to February, November to January, and December in the southern hemisphere is an axis of symmetry, as well as June in the northern hemisphere (Britton, 1986).…”
Section: Qualitative Characteristics Of Solar Radiationmentioning
confidence: 99%
“…At the summer solstice, the presented pattern shifts by 23° toward the North Pole, and at the winter solstice, it shifts by 23° toward the South Pole. This shift determines the seasonal specificity of the corolla coloration in flowering plants (Britton, 1986). The longwave boundary of solar radiation can also cause the appearance of adaptive white surface due to the adaptation to numerous peaks in the IR range (Figure 1).…”
Section: Qualitative Characteristics Of Solar Radiationmentioning
confidence: 99%
“…1 A number of reviews have dealt with natural sesquiterpenoids, 2-7 diterpenoids, [8][9][10][11] sesterterpenoids, 12,13 triterpenoids, [14][15][16][17][18] carotenoids and polyterpenoids. [19][20][21][22][23] Other general reviews are: "Marine natural products". [24][25][26][27][28][29][30] In this review, we show structures of linear furano-and pyrroloterpenoids, and previously reported linear furano-and pyrroloterpenoids where there has been a structural revision or a newly established stereochemistry, previously reported linear furano-and pyrroloterpenoids for which rst syntheses, new bioactivities, or new sources are described are referenced, and this review also added the furanotetraterpenoids and furanocarotenoids.…”
Section: Introductionmentioning
confidence: 99%